PENGARUH KOMPETENSI, PENGALAMAN KERJA DAN PENEMPATAN KERJA TERHADAP KOMITMEN ORGANISASi PT. WAHANA META RIAU DI PEKANBARU - Bram Afrilyan; Kurniawaty Fitri; Marhadi ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Wahana Meta Riau, Pekanbaru. The purpose of this study was to determine the effect of competence, work experience and job placement on organizational commitment. The study population was 75 employees and is set with models census. Research variables used are the competencies, work experience and job placement as independent variables and organizational commitment as dependent variable. Methods of data analysis using multiple linear regression analysis aided by SPSS version 21.The results of this study concluded that the variable competence, work experience, and job placement positive and significant effect on organizational commitment. In terms of competence, the company should improve the competence of employees through technical training related to the field of the employee's duties. Work experience can be enhanced by the company's employees through the implementation of tasks in accordance with the ability of employees so that employees will increasingly gain work experience. In the variable job placement for the implementation is effective and appropriate, where the company should have to look at the educational background, skills suitability, suitability of the attitude of the employees. Regarding the commitment needs to be improved is the attention of the employees of the various problems faced by the company, so that organizational goals can be achieved.Keyword: Competence, Work Experience, Job Placement, Organizational Commitment